2011
DOI: 10.1002/jmv.22160
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus genotype G: Prevalence and impact in patients co‐infected with human immunodeficiency virus

Abstract: Relatively little is known about the role of hepatitis B virus (HBV) genotype G (HBV/G) in patients co-infected with human immunodeficiency virus (HIV) and HBV. This study examined the prevalence and association of HBV/G to liver fibrosis in co-infected patients. HBV genotypes were determined by direct sequencing of the HBV surface gene or Trugene® HBV 1.0 assay in 133 patients infected with HIV/HBV. Quantitative testing of HBV-DNA, HBeAg, and anti-HBe were performed using the Versant® HBV 3.0 (for DNA) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 43 publications
(54 reference statements)
2
18
0
Order By: Relevance
“…All 10 HBV-G infections concerned men that were also infected with HIV-1. Studies from other countries report a similar association of HBV-G infection with HIV-infection and with the MSM risk group [22,25,26,30,31]. In our study, only four HBV-A/G infected patients could be positively identified as MSM, for five others the risk factor was not stated.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…All 10 HBV-G infections concerned men that were also infected with HIV-1. Studies from other countries report a similar association of HBV-G infection with HIV-infection and with the MSM risk group [22,25,26,30,31]. In our study, only four HBV-A/G infected patients could be positively identified as MSM, for five others the risk factor was not stated.…”
Section: Discussionsupporting
confidence: 65%
“…HBV-G strains isolated worldwide show very little genetic variation compared to other HBV genotypes [10]. There are indications that mixed HBV infections that include an HBV-G strain are associated with increased liver fibrosis [27,28,30], suggesting that patients infected with HBV-G should be monitored more closely. Also, response to antiviral treatment has been reported to be less effective in patients co-infected with HBV-G as compared to single genotype infections [23].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have suggested that HBV genotype G may require HBV co-infection with another genotype. The presence of infection with HBV genotype G found to be an independent risk factor for fibrosis progression in a French study of patients diagnosed with HBV and HIV coinfection [75,76]. The frequent finding of HBV G in co-infected patients and its association with more advanced fibrosis, suggests that this genotype leads to more rapid liver disease progression.…”
Section: Hbv Genotype D and Disease Outcomementioning
confidence: 92%
“…Here, the patient reported sexual intercourse with several men and concurrently acquired HBV as well as HAV and HIV earlier in his life. Of note, he became infected with HBV genotype G, which is rare in France and worldwide but has been described to be more frequent in HIV-infected patients (34)(35)(36) and particularly among MSM (37)(38)(39). Also, we searched for top hits in the NCBI sequence database with the HAV sequence recovered from a patient's serum collected 1 year before HEV-HBV primary infection, and we found three HAV sequences with 100% nucleotide identity that were obtained from serum samples of MSM in Barcelona, Spain (40).…”
mentioning
confidence: 99%